2017
DOI: 10.1161/atvbaha.116.308187
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Overexpression of Intracellular NAMPT Attenuates Atherosclerosis by Regulating PPARγ-Dependent Monocyte Differentiation and Function

Abstract: This study highlights the functional dichotomy of intracellular versus extracellular NAMPT, and unveils a critical role for the iNAMPT-peroxisome proliferator-activated receptor γ axis in atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…26) However, another study showed that the overexpression of NAMPT in leukocytes in atherosclerotic patients can inhibit atherosclerosis by the regulation of PPARγ dependent monocyte differentiation. 27) The results of this study showed that the levels of iNAMPT and Sirt1 in PBMC and NAD+, eNAMPT in plasma increased in the ACS patients, which suggested that the NAMPT/NAD+/Sirt1 signaling pathway was upregulated in the ACS patients. Sirt1 is a histone deacetylase that depends on NAD+; it has the function of inhibiting apoptosis, inhibiting inflammatory reaction, and inhibiting oxidative stress injury.…”
Section: Discussionmentioning
confidence: 63%
“…26) However, another study showed that the overexpression of NAMPT in leukocytes in atherosclerotic patients can inhibit atherosclerosis by the regulation of PPARγ dependent monocyte differentiation. 27) The results of this study showed that the levels of iNAMPT and Sirt1 in PBMC and NAD+, eNAMPT in plasma increased in the ACS patients, which suggested that the NAMPT/NAD+/Sirt1 signaling pathway was upregulated in the ACS patients. Sirt1 is a histone deacetylase that depends on NAD+; it has the function of inhibiting apoptosis, inhibiting inflammatory reaction, and inhibiting oxidative stress injury.…”
Section: Discussionmentioning
confidence: 63%
“…In contrast, knockdown of PPAR␥ impairs M2 polarization and insulin signaling (10). It has been demonstrated that PPAR␥-dependent monocyte differentiation into M2 macrophage is beneficial to human carotid atherosclerosis (11). PPAR␥ activation by pioglitazone regulates M2 macrophage infiltration and stabilizes the neovessels in the infarct border zone, leading to a better outcome for patients after stroke (12).…”
mentioning
confidence: 99%
“…Recent studies have been focused on eNAMPT, which is thought to act as a pro‐inflammatory cytokine (Laiguillon et al, ). However, Lin et al () and our research group also reported that iNAMPT may have beneficial anti‐inflammatory properties (Bermudez et al, ). In the present study, this dual role of eNAMPT (visfatin) and iNAMPT has been explored by analyzing the concentration of visfatin/eNAMPT in the medium of cells and the relative mRNA levels of NAMPT/iNAMPT .…”
Section: Discussionmentioning
confidence: 79%
“…In the rescue route of nicotinamide adenine dinucleotide (NAD + ) generation, intracellular NAMPT ( iNAMPT ) appears to be the rate‐limiting enzyme (Montserrat‐de la Paz, Naranjo, et al, ). Previous studies have proved the significance of NAMPT‐mediated NAD + recycling, in cooperation with NAD + ‐dependent protein deacetylases (sirtuins), directly on the expression of peroxisome proliferator‐activated receptors ( PPARs ), NF‐κB , and endothelial NOS ( eNOS ); many data also provide evidence of an indirect role in metabolism, aging, inflammation, cell proliferation, and differentiation (Bermudez et al, ). Cells also produce NAMPT to create an extracellular supply (eNAMPT) with cytokine‐like activity (Dahl, Holm, Aukrust, & Halvorsen, ).…”
Section: Introductionmentioning
confidence: 99%